Pectin Microspheres: Synthesis Methods, Properties, and Their Multidisciplinary Applications - Keila Gutierrez-Alvarado; Randall Chacón-Cerdas; Ricardo Starbird-Perez (Chemistry, 2022)
There is great contemporary interest in using cleaner technologies through green chemistry and utilizing biopolymers as raw material. Pectin is found on plant cell walls, and it is commonly extracted from fruit shells, mostly apples or citrus fruits. Pectin has applications in many areas of commercial relevance; for this reason, it is possible to find available information about novel methods to transform pectin and pursuing enhanced features, with the structuring of biopolymer microspheres being highly cited to enhance its activity. The structuring of polymers is a technique that has been growing in recent decades, due to its potential for diverse applications in various fields of science and technology. Several techniques are used for the synthesis of microspheres, such as ionotropic gelation, extrusion, aerosol drying, or emulsions, with the latter being the most commonly used method based on its reproducibility and simplicity. The most cited applications are in drug delivery, especially for the treatment of colon diseases and digestive-tract-related issues. In the industrial field, it is used for protecting encapsulated compounds; moreover, the environmental applications mainly include the bioremediation of toxic substances. However, there are still many possibilities for expanding the use of this biopolymer in the environmental field.